Using Multipath Priority Routing for Solar Powered Wireless Sensor Networks - Thirumal, Kandasamy; Jaya Kumar, Krishnan (2008)
Constant growth in the wireless sensor network (WSN) needs routing protocol which can cater for renewable energy sources as compared to conventionally used non-renewable energy sources in sensor nodes. APPOLO algorithm is used to periodically and locally determine the topological knowledge range of each solar-powered node, based on an estimated energy budget for the following period. Energy budget includes current energy, the predicted energy consumption and the energy expected from the solar cell. PISA is a QoS aware routing used for route selection based on objective. Priority based routing in solar powered wireless sensor network is implemented using APOLLO and PISA. Thus energy saving is attained for real-time route discovery. In this paper, multipath non-redundant data dissemination approach is used for the priority based routing scheme to further optimize use of energy in wireless sensor network.